2012
DOI: 10.1111/j.1399-3062.2012.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Demodicidosis simulating acute graft‐versus‐host disease after allogeneic stem cell transplantation in one patient with acute lymphoblastic leukemia

Abstract: One important differential diagnosis of facial erythema in a patient receiving an allogeneic bone marrow transplant (BMT) is acute graft-versus-host disease (GVHD). Demodex folliculorum has been rarely implicated in the development of facial rashes in immunosuppressed patients, including BMT recipients. We report the case of a patient, suffering from acute lymphoblastic leukemia, who after bone marrow transplantation developed a facial rash due to D. folliculorum mimicking GVHD. Differential diagnosis of facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…8 Demodicosis have been described predominantly in 3 facial skin conditions: pityriasis folliculorum, rosacea-like demodicosis, and "demodicosis gravis." 17 Because Demodex mites are saprophytes in the human skin, a casual relationship with these pathologies has been controversial. 17 Because Demodex mites are saprophytes in the human skin, a casual relationship with these pathologies has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…8 Demodicosis have been described predominantly in 3 facial skin conditions: pityriasis folliculorum, rosacea-like demodicosis, and "demodicosis gravis." 17 Because Demodex mites are saprophytes in the human skin, a casual relationship with these pathologies has been controversial. 17 Because Demodex mites are saprophytes in the human skin, a casual relationship with these pathologies has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…18 We present 2 patients in which FM was found in the drug-related vasculitis and demodecidosis 19 after BMT for nasal-type T/NK-cell lymphoma and multiple myeloma, respectively (Fig. 19 Infectious-related FM has also been communicated in the setting of human immunodeficiency virus 20 and herpes zoster virus. Both these cases showed polyclonality, no atypical mitotic figures, no recurrences of their underlying hematologic malignancy, and lack of progression to lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…In cancer patients who were taking epidermal growth factor receptor inhibitors, it was reported that Demodex mite colonization was increased which increased the risk of dermatologic conditions such as annular facial eruptions. There were also reported cases of Demodex folliculitis mimicking acute cutaneous graft-versus-host disease (GVHD) 2126. Tissue samplings of the affected skin tissue confirmed the diagnosis of Demodex in the suspected GVHD patients.…”
Section: Pathogenesismentioning
confidence: 89%